MUI’S Role Regarding Halal Certification Viewed from Law Number 33 of 2014 Concerning Halal Product Guarantees (Case Study of Medan Branch Mixue Drink Company) - Afif Syahputra; Syafruddin Syam (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Mixue Ice Cream & Tea is a Chinese franchise that has been around since June 16th, 1997. Mixue has been in Indonesia since 2020, first in the city of Bandung, and now has more than a thousand locations throughout the country, with the majority in the city of Medan. Since Medan City is home to a sizable Muslim population, it offers several possibilities for economic expansion. The purpose of this analysis is to examine the function of the MUI in relation to halal certification based on the JPH Law (No. 33 of 2014). This research relies on qualitative research techniques. Taking a normative legal approach to the pressing problem of research by analyzing the steps used to obtain halal certification of Mixue drinks. The findings of this study led to a request from the Indonesian Ministry of Religion BPJH that Mixue refrain from using the halal symbol on its packaging before the halal certificate is issued. Mixue Ice Cream & Tea has been declared Halal by the MUI. After a hearing regarding halal products was conducted by the Fatwa Commission on 15th February 2023, the MUI issued a Halal Decree. The head of the Halal Inspection Agency, the Food, Drug, and Cosmetic Review Institute, presented an audit report on halal certification to the MUI, and after careful deliberation, the organization issued a Halal Decree. MUI issues Halal Decree. The Head of the Halal Inspection Agency of the Food, Drug, and Cosmetic Review Institute presented the audit report on halal certification to the MUI, and after careful consideration, the organization issued a Halal Decree. MUI issues Halal Decree. The head of the Halal Inspection Agency, the Food, Drug, and Cosmetic Review Institute, presented an audit report on halal certification to the MUI, and after careful deliberation, the organization issued a Halal Decree.